Supramolekularni tekoče-kristalinični poliuretan - Ambrožič, Gabriela (Materiali in tehnologije, 2000)
In this paper, the synthesis and characterization of liquid crystalline hydrogen-bonded side-chain polyurethane is presented. It was prepared by the molecular recognition through the single hydrogen bond between the piridyl unit on a polyurethane backbone and a mesogenic 4-dodecyloxybenzoic acid. The liquid-crystalline properties were determined by differential scanning calorimetry, polarizing optical microscopy and X-rayx diffractometry.
Keywords: supramolekularna kemija; polimeri; poliuretan; sinteza; karakterizacija